Fuel characteristics and fire behavior in Melaleuca peat forest, southern Thailand - Chairak, Sutthiphong; Wanthongchai, Kobsak; Ketpraneet, San; Thaopimai, La-ongdao (Agriculture and Natural Resources, 2026)
Importance of the work: Understanding fire behavior in peat forest dominated by Melaleuca cajuputi is very important for precision fire management. Objectives: To examine fuel characteristics and fire behavior using systematic burning experiments in peat forest dominated by M. cajuputi. Materials and Methods: Three vegetation types were investigated (lowland and upland forest stands of pure M. cajuputi and a grassland) in Khuan Khreng tropical peat forest, with four replicated plots (each 30 × 30 m) of each vegetation type. The fuel and fire behavior were investigated. Results: The aboveground fuel consisted of litter, undergrowth, leaves and bark, of which the litter and undergrowth dominated in the Melaleuca stands and grassland, respectively. Total aboveground fuel loads in the upland and lowland forests and the grassland were 23.28 t/ha, 15.84 t/ha and 13.21t/ha, respectively. The heat value of Melaleuca bark was measured at 5,503 cal/g. The average peat depth was 1.4 m, with a bulk density of 0.23 g/cm3 , while the deepest recorded peat layer reached 3.10 m. The grassland fires exhibited very active fire behavior, with a rapid spread rate of 4.01 m/min and a flame length of 1.3 m, surpassing the fire behavior in the Melaleuca stands. The grassland fires were classified as medium intensity (639 kW/m), whereas the fires in the lowland and upland M. cajuputi areas were of lower intensity (120 kW/m and 152 kW/m, respectively). The laboratory experiments showed that the peat smoldered for several days with a slow spread rate of 3.24 cm/hr, while temperatures typically exceeded 620 °C. Main finding: Peat forests contain substantial fuel loads, comprising both aboveground vegetation and belowground peat deposits. Often, the direction of peat combustion is unpredictable and detection is challenging. Consequently, peat fire behavior tends to be intense and can result in severe ecological and environmental impacts.